High-Voltage Gain DC-DC Converter For Photovoltaic Applications In DC Nanogrids - Pontes, Yury; Elmano de Alencar e Silva, Carlos; Mineiro Sá Junior, Edilson (Eletrônica de Potência, 2020)
Photovoltaic (PV) systems used in DC Nanogrids present prominent advantages associated with low maintenance need and operation costs. Owing to the low output voltage of the PV module, highly efficient high-voltage gain DC-DC converters are required for connection with the DC nanogrid. This work presents a novel DC-DC converter topology with current source characteristic for PV applications and current injection in DC nanogrids. The introduced converter uses coupled inductors and switched capacitors to achieve high voltage gain with low component count and without using extreme duty ratios. Besides, the main switch is turned on with nearly zero current, thus contributing to minimized switching losses. The qualitative and quantitative analyzes of the circuit are presented in detail and a prototype rated at 200 W is developed and evaluated in the laboratory. Experimental results demonstrate efficient renewable energy conversion, where the maximum efficiency is 96.8%.